Participação pública em programas ambientais :um estudo em área suscetível à desertificação no Estado do Rio Grande do Norte - Vianna, Francisco Magno de Albuquerque (2006)
The natural resources degradation and its consequences to the society life have provided several discussions about the evaluation methods and environmental management, and the available means to minimize the effects of man s actions over the environment. Amongst these actions is the encouragement to the community participation in the process of carrying out the environmental programs, considering government and enterprises representatives or residents of certain places as social actors. Within these context, this paper had as a goal the investigation of the public participation in the environmental programs in areas that are susceptible to desertification, specificly in Parelhas/RN. The choice for this town was due to its insertion in an area considered as a desetification nucleous, which is, a region that suffers land degradation as a consequence of climate variations or human activities. Therefore, the research in question, of a descriptive and exploratory type, had as an instrument a structured questionnaire, applied to a sample of 223 people out of an 11,068 over 20 years of age residents population. The data have been tabled from Statistics for Windows Program and later interpreted based on the theoretical reference over the subject. As a result, corroborating to the literature of the area, it was found that the community participation in any type of action or debate about environmental questions is associated to the perception and knowledge about the problems. Although the people who were interviewed believe in the responsibility of the ceramic industry in causing environmental problems, they also believe that the benefits brought by the sector overcome such problems